Jenis kanker dengan kualitas hidup pada pasien kanker - Aisah, Mugni; Prasestiyo, Hamudi; Widiastuti, Widiastuti (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Cancer is a chronic disease that not only affects physical conditions but also influences patients’ psychological, social, and environmental aspects. Differences in cancer types may lead to variations in symptoms, treatment processes, and patients’ responses to the disease, which potentially affect quality of life. Purpose: To determine the relationship between cancer type and quality of life among cancer patients. Method: This study is a quantitative research with a descriptive-analytic design and a cross-sectional approach. The study population consisted of 173 cancer patients, with a total sample of 70 respondents selected based on inclusion and exclusion criteria using a purposive sampling technique. The type of cancer was measured using respondents’ characteristic data, while quality of life was assessed using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). Data were analyzed using Kendall’s Tau correlation test. Results: Most respondents had breast cancer (85.7%) and good quality of life (92.9%). Kendall’s Tau correlation test showed no significant relationship between cancer type and quality of life, with a p-value of 0.056 >0.05 and a correlation coefficient of -0.185. Conclusion: There was no significant relationship between cancer type and quality of life among cancer patients. The strength of the relationship between the two variables was categorized as very weak with a negative direction, indicating an inverse or non-proportional relationship.   Keywords: Cancer; Cancer Type; Quality Of Life.   Pendahuluan: Kanker merupakan penyakit kronis yang tidak hanya berdampak pada kondisi fisik, tetapi juga memengaruhi aspek psikologis, sosial, dan lingkungan pasien. Perbedaan jenis kanker dapat menyebabkan variasi gejala, proses pengobatan, serta respons pasien terhadap penyakit, yang berpotensi memengaruhi kualitas hidup. Tujuan: Untuk mengetahui hubungan antara jenis kanker dengan kualitas hidup pasien kanker. Metode: Penelitian ini merupakan penelitian kuantitatif dengan desain deskriptif analtik dan pendekatan cross sectional. Populasi penelitian berjumlah 173 pasien kanker dengan jumlah sampel sebanyak 70 responden yang dipilih dengan kriteria inklusi dan ekslusi menggunakan teknik purposive sampling. Jenis kanker diukur menggunakan data karakteristik responden, sedangkan kualitas hidup diukur menggunakan kuesioner European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). Teknik Analisa data menggunakan uji korelasi Kendall’s Tau. Hasil: Sebagaian besar responden memiliki jenis kanker payudara (85,7%) dan kualitas hidup baik (92,9%). Uji korelasi Kendall’s Tau menunjukan tidak ada hubungan antara jenis kanker dengan kualitas hidup pada pasien kanker dengan nilai p-value = 0.056 < 0.05 dan koefisien korelasi -0.185. Simpulan: Tidak terdapat hubungan yang signifikan antara jenis kanker dengan kualitas hidup pada pasien kanker dan tingkat keeratan hubungan kedua variabel ini di kategorikan sangat rendah dengan arah hubungan negatif yang memiliki makna hubungan berlawanan atau tidak berbanding lurus.   Kata Kunci: Jenis Kanker; Kanker; Kualitas Hidup.